1988
DOI: 10.1111/j.1399-3054.1988.tb05434.x
|View full text |Cite
|
Sign up to set email alerts
|

Epi‐ and intracuticular lipids and cuticular transpiration rates of primary leaves of eight barley (Hordeum vulgare) cultivars

Abstract: The major constituents of the epi‐ and intracuticular lipids of primary leaves of 8 cultivars of barley (Hordeum vulgare L.) have been studied together with cuticular transpiration rates. The total amount of analysed cuticular lipids ranged from 9.6 to 13.4 μg cm−2 and was dominated by the epicuticular fraction, which made up 73–84% of the total. There were variations in the percentages of the analysed lipid classes, alkanes, esters, aldehydes, β‐diketones and alcohols, between epi‐ and intracuticular lipids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…TR st is controlled by stomatal conductance, largely determined by tissue water status at a given vapour pressure difference between the leaf surface and the air. TR cu is affected by the physiocochemical characteristics of the leaf surface, such as wax thickness and, to a greater extent, wax microstructure, which largely determine the leaf surface's hydraulic permeability and transport characteristics (Svenningsson, 1988; Xu et al ., 1995, reviewed by Riederer & Schreiber, 1996; Schreiber et al ., 1996). Under extreme water deficit, stomata close and stomatal conductance falls, and water loss by the cuticular route becomes significant (Fig.…”
Section: Water Salinity and Cold Stressmentioning
confidence: 99%
“…TR st is controlled by stomatal conductance, largely determined by tissue water status at a given vapour pressure difference between the leaf surface and the air. TR cu is affected by the physiocochemical characteristics of the leaf surface, such as wax thickness and, to a greater extent, wax microstructure, which largely determine the leaf surface's hydraulic permeability and transport characteristics (Svenningsson, 1988; Xu et al ., 1995, reviewed by Riederer & Schreiber, 1996; Schreiber et al ., 1996). Under extreme water deficit, stomata close and stomatal conductance falls, and water loss by the cuticular route becomes significant (Fig.…”
Section: Water Salinity and Cold Stressmentioning
confidence: 99%
“…The bulk wax extracts might consequently reflect surface composition only if both wax layers had similar composition. But this second assumption has repeatedly been challenged by studies that showed compositional gradients between intracuticular and epicuticular waxes of diverse species (Haas and Rentschler, 1984;Svenningsson, 1988). Hence, all those previous wax analyses relying on extraction lacked the necessary spatial resolution to accurately assess surface composition.…”
mentioning
confidence: 99%
“…If most of the water transport across the epidermal membrane takes place through structural defects in the soluble cuticular lipid barrier, as proposed by Schonherr et al (1984), only small contributions of extra lipids or minor differences in liquid morphology could significantly reduce the t r a n sport through these pathways (Svenningsson 1988). This may explain our results as well as some of the inconsistencies mentioned earlier.…”
Section: Biotechnic and Histochemistrymentioning
confidence: 54%
“…This may explain our results as well as some of the inconsistencies mentioned earlier. Differences among genotypes might be too small to detect with traditional lipid analysis techniques (Svenningsson 1988), which could explain why cuticular transpiration rates are considerably altered in response to a drought s t r e s s treatment (Araus et al 1991, Larsson a n d Svenningsson 1986), yet no clear correlation d u e to drought s t r e s s could be observed among changes in cuticular transpiration, soluble cuticular lipid levels (Svenningsson 1988), or epicuticular wax load (Larsson a n d . Great variations in cuticular conductance have also been reported in species depending on age (Viougeas et al 1995), t h e immediate environment during growth ( J o r d a n et al 1984), different a r e a s of t h e s a m e plant and leaf (Schonherr 1982), temperature , light intensity, and most pronouncedly with humidity (Van Gardinger a n d Grace 1992).…”
Section: Biotechnic and Histochemistrymentioning
confidence: 99%